What Do We Mean by Performativity in Organizational and Management Theory? The Uses and Abuses of Performativity. (7th July 2015) - Gond, Jean‐Pascal; Cabantous, Laure; Harding, Nancy; Learmonth, Mark
Abstract : John Austin introduced the formulation 'performative utterance' in his 1962 book How to Do Things with Words . This term and the related concept of performativity have subsequently been interpreted in numerous ways by social scientists and philosophers such as Lyotard, Butler, Callon and Barad, leading to the coexistence of several foundational perspectives on performativity. This paper reviews and evaluates critically how organization and management theory (OMT) scholars have used these perspectives, and how the power of performativity has, or has not, stimulated new theory‐building. In performing a historical and critical review of performativity in OMT, the authors' analysis reveals the uses, abuses and under‐uses of the concept by OMT scholars. It also reveals the lack of both organizational conceptualizations of performativity and analysis of how performativity is organized. Ultimately, the authors' aim is to provoke a 'performative turn' in OMT by unleashing the power of the performativity concept to generate new and stronger organizational theories.